Descriptive analysis of histological types in women undergoing post mastectomy breast reconstruction - Reyes-Gómez, Victor Alfonso; Ramírez-Guerrero, Rene Oliver; Moreno-Hernández, Sergio G.; Martínez-Martínez, Grecia C.; Mejía-Rivera, Samaria E.; Torres-Piña, Raymundo (International Journal of Research in Medical Sciences, 2023)
Background: Breast cancer is a pathological entity that widely compromises the life and quality of life of affected women; in addition to the great affectation to the current health services. Therefore, maintaining an accurate and complete cancer registry program is one of the most important factors in implementing national cancer control programs and evaluating the results of screening, diagnosis, and treatment. Among the current limitations in the studies, there is a gap in the study of the population undergoing breast reconstruction. Methods: A retrospective study was carried out at hospital general de México “Dr. Eduardo Licéaga” with the information from the clinical records of the period 2019-2020. Patients undergoing breast reconstruction after mastectomy with histological report were included. Through non-probabilistic sampling, a population of 138 women was formed. For data analysis, frequencies and percentages were calculated for the qualitative variables; while for the quantitative variables, mean and standard deviation were calculated. Results: 138 women who underwent breast reconstruction were included, the mean age was 49.9±10.85 years, the mean BMI was 26.80±4.62 kg/m2, the secondary educational level predominated (34.8%), radiotherapy was applied to 34.1%, reconstruction was late in 75.4%, the most frequent reconstruction technique was TRAM flap (44.2%), the histological type of invasive ductal carcinoma predominated (68.1%). Conclusions: In women undergoing post-mastectomy breast reconstruction, the histological type of invasive ductal carcinoma predominates.